HEAT TRANSFER PERFORMANCE OF MHD NANOFLUID FLOW IN CORRUGATED ENCLOSURES WITH DIFFERENT INTERNAL HEAT SOURCE CONFIGURATIONS (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
The natural convection in a corrugated enclosure with the porous medium and filled with nanofluid with magnetic field was investigated. The numerical method was used to obtain the stream function for several inclinations of the magnetic field (γ = 0°, 45°, and 90°). The Darcy number that was a function of the range from 10⁻³ to 10⁻⁵, was maintained and Rayleigh (Ra = 10⁶) and Hartmann, Ha =60) numbers held fixed. The intensities of the fluid circulation strength were found to increase with increasing (γ), and maximum stream function strength was obtained at γ = 90°. Further, increasing the permeable resistance (decreasing Da) decreased fluid flow and suppressed natural convection. The overlay of the contours of temperature and streamline points to the contributions of both magnetic alignment and porous resistance in heat transfer. These findings emphasize the necessity of selecting appropriate magnetic orientation and porosity value to enhance maximum thermal efficiency in magneto-convective engineering systems.